VD_FINDINFO Faillite / 2014 / 36 vom 26. November 2014 - VD Tribunal cantonal (2014)
OUVERTURE DE LA FAILLITE, INSOLVABILITÉ, FICTION DE LA NOTIFICATION | 174 al. 1 LP, 174 al. 2 LP, 174 LP, 138 al. 1 CPC (CH), 138 al. 3 let. a CPC (CH)